Pelatihan Pencatatan Laporan Keuangan Sederhana Berbasis Digital melalui Aplikasi TokoKu pada UMKM di Desa Kebapangan - Rani Titi Rohmani; Ratri Paramitalaksmi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Training activities for recording simple digital-based financial reports through the TokoKu application were carried out with the participant Mrs. Ngadiyah, owner of Warung Snacks and Sembako Hidayah. This training aims to help MSMEs overcome the problems of disorganized manual recording, minimal understanding of financial reports, and limited use of technology. This activity is carried out in three stages: preparation, implementation, and mentoring. The results of the training showed an increase in participants' ability to record transactions, prepare simple financial reports, and manage inventory more efficiently. The TokoKu application also helps reduce recording errors and makes business decision making easier. Even though there are obstacles related to technology adaptation and poor internet access, this training succeeded in proving that digitalization can increase the sustainability and competitiveness of MSMEs in the digital era.